Eksistensi Putusan Basyarnas Dalam Eksekusi Hak Tanggungan Terhadap Sengketa Perbankan Syariah - Andi Sunarti; Yuhelson Yuhelson; Erny Kencanawati (JOURNAL of LEGAL RESEARCH, 2022)
Settlement of problems that arise in sharia banking contracts for guarantees of mortgage rights is based on the binding principle of the contract (Mabda' Wujub Al Wafa' Bi Al' Aqad/Asas Pacta Sunt Servanda) which means that the contract of the parties made legally binds the parties as a law. In the settlement of disputes in one of the financing contracts through Islamic banking, there are options for settlement methods including settlement by deliberation and consensus, settlement through Alternative Dispute Resolution (APS), including Mediation, Arbitration, Conciliation, and Expert Assessment and settlement through the Religious Courts. This type of research uses descriptive qualitative research methods. Basyarnas was formed because PA at that time did not yet have the authority to examine Islamic economic cases, so Basyarnas was formed because of an urgent need to resolve the possibility of civil disputes between Islamic banks and customers.